Lived experiences of dysphagia-related quality of life among esophageal cancer patients: a qualitative study - Tseganesh Asefa; Winta Tesfaye; Gedamnesh Bitew; Hiwot Tezera (Health and Quality of Life Outcomes)
Abstract Introduction Esophageal cancer impairs basic functions such as eating and drinking frequently resulting in difficulty swallowing (dysphagia) and other problems such as weight loss, pain, fatigue, and taste alterations. There is still a research gap in understanding the impact of dysphagia on quality of life, as patients continue to bear significant physical and psychological burdens despite advances in treatment. This study attempted to address this gap by examining the lived experiences of dysphagia-related quality of life among esophageal cancer patients. Methods A phenomenological study was employed to analyze the data provided by 14 patients with esophageal cancer at the Oncology Center of the University of Gondar Comprehensive Specialized Hospital from March to April 2023. An interview guide was employed to carry out in-depth interviews with purposively selected patients. The interviews were audio-taped, translated, transcribed, and analysed using thematic analysis. Results Three main themes emerged from the analysis of the participant interviews: physical challenges related to difficulty swallowing, altered dietary habits, and struggle to maintain weight; psychosocial strain, including emotional distress and social isolation; and reliance on assistance, encompassing both dependency and financial burden. Conclusion and recommendations This study underscores the significant physical, emotional, and social challenges experienced by esophageal cancer patients with dysphagia. To enhance support, healthcare providers should develop personalized care plans that address both the physical and emotional aspects of dysphagia, with sensitivity to cultural practices. Efforts should also be made to alleviate feelings of dependency and promote public awareness to reduce stigma and build a more supportive community.